2009
DOI: 10.1155/2009/469480
|View full text |Cite
|
Sign up to set email alerts
|

Improved Reproduction of Stops in Noise Reduction Systems with Adaptive Windows and Nonstationarity Detection

Abstract: A new block-based noise reduction system is proposed which focuses on the preservation of transient sounds like stops or speech onsets. The power level of consonants has been shown to be important for speech intelligibility. In single-channel noise reduction systems, however, these sounds are frequently severely attenuated. The main reasons for this are an insufficient temporal resolution of transient sounds and a delayed tracking of important control parameters. The key idea of the proposed system is the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Evaluating the ztransforms on the unit circle, the higher frequency resolution in X l (z) implies that h L [n] has a more narrow lowpass frequency response than h K [n] and that L > K. It has been shown that WOLA filter banks with longer prototype filters, such as h L [n], can still be synthesized with the same low delay as h K [n], see for instance [12], [13], [14]. The HRFB gives an improved frequency resolution representation of x[n] under the assumption that the signal is stationary over L samples.…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…Evaluating the ztransforms on the unit circle, the higher frequency resolution in X l (z) implies that h L [n] has a more narrow lowpass frequency response than h K [n] and that L > K. It has been shown that WOLA filter banks with longer prototype filters, such as h L [n], can still be synthesized with the same low delay as h K [n], see for instance [12], [13], [14]. The HRFB gives an improved frequency resolution representation of x[n] under the assumption that the signal is stationary over L samples.…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…In one implementation [15], the weighted summation of the first derivative of signal energy in four frequency regions of up to 5.5 kHz is used as a measure to mark the transient segment of the speech signal. The transient is also detected by a likelihood ratio measurement of statistical similarity of two block of data to decide whether the signal has stayed stationary or its statistical characteristics have changed, hence signifying a transient event [10].…”
Section: Detection Of Boundary Of Speech Utterancementioning
confidence: 99%
“…Tests based on informal subjective listening suggest that higher gain values (~ 4dB) can be applied at high SNR values, however this gain needs to be reduced as the SNR deteriorates. A similar method is suggested in [17] to improve the intelligibility of speech signal in the presence of background noise and deployed in [10] for a noise reduction algorithm with a switching analysis/synthesis filter bank structure. .…”
Section: Fig 2 Time Domain Filters and Their Group Delaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have proposed noise estimation schemes for unknown noise signals [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The minimum statistics (MS) noise estimation scheme [7] is one that works well in nonstationary noisy environments.…”
Section: Introductionmentioning
confidence: 99%